Migraciones, crisis y pandemias en el siglo XXI Argentina, Chile y Uruguay - Silva, Hernán Asdrúbal (Ariadna Ediciones, 2021)
The migration issue, which is presented as one of the most current socio-economic and political problems, when combined with the cataclysm produced by the COVID pandemic, acquires new dimensions. We have approached this project of the PAIGH-OAS, knowing that on the one hand it is transcendental for the Inter-American System due to its connotations and implications and that on the other, we do it both as historians and actors. Double challenge for having to analyze the processes in scientific terms and in turn in first person, events that have involved us since their origins and are still valid due to the uncertainty that this complex disease continues to cause in the world.